Performance of Broilers Fed Raw Bambarra Groundnut [Vigna subterranean (L.) Verdc] Offal Diets Supplemented with Lysine and or Methionine - Ukpabi, U.H.; Amaefule, K.U.; Amaefule, O. M. (International Journal of Poultry Science, 2008)
One hundred and twenty 3-week old Anak broilers were used to evaluate the performance, feed cost and apparent nutrient digestibility coefficients of raw Bambarra Groundnut Offal (BGO) diets supplemented with lysine and or methionine. The experimental design was Completely Randomized Design (CRD) with each treatment replicated three times. Five treatment diets were formulated to be isoenergetic and isonitrogenous. The inclusion level of the bambarra groundnut offal in diets 2, 3, 4 and 5 was 20%. Diet 1 (control) had no BGO, lysine or methionine supplementation while diets 2, 3, 4 and 5 were supplemented with lysine, methionine, lysine + methionine and no supplementation, respectively. Parameters measured were final live weight, daily weight gain, feed intake, Feed Conversion Ratio (FCR), Protein Efficiency Ratio (PER), feed cost and apparent nutrient digestibility coefficients. Results showed that broilers fed diet 4 supplemented with lysine+methionine had improved FCR (2.05) and PER (2.37) than broilers fed other diets and was consistently similar to the control diet in all parameters measured. There were no significant (P>0.05) differences among the broilers fed the various diets in feed cost indices measured, except cost per kg feed. Broilers fed diet 4 supplemented with lysine and methionine had the highest apparent digestibility coefficient of protein (59.39%) while broilers fed diet 5 without amino acid supplementation had the lowest (52.78%). The conclusion was that raw bambarra groundnut offal should be supplemented with lysine and methionine to improve broiler FCR, PER, digestibility coefficient of CP and reduce feed cost.